Challenging the Conventional Wisdom on Active Management: A Review of the Past 20 Years of Academic Literature on Actively Managed Mutual Funds. Issue 4 (2nd October 2019) - Cremers, K.J. Martijn; Fulkerson, Jon A.; Riley, Timothy B.
Abstract : Just over 20 years have passed since the publication of Mark Carhart's landmark 1997 study on mutual funds. Its conclusion—that the data did "not support the existence of skilled or informed mutual fund portfolio managers"—was the capstone of an academic literature, which began with Michael Jensen in 1968, that formed the conventional wisdom that active management does not create value for investors. We review the literature on active mutual fund management since the publication of Carhart's work to assess the extent to which current research still supports the conventional wisdom. Our review of the most recent literature suggests that the conventional wisdom is too negative on the value of active management. Abstract : Disclosure: This research was supported by the Investment Adviser Association's Active Managers Council. Martijn Cremers currently serves as an independent director at Ariel Investments and a consultant to Touchstone Investments and State Street Associates. Editor's note Submitted 27 January 2019 Accepted 23 May 2019 by Stephen J. Brown